Mental Health with Gender Differences in Internet Pornography-Viewing-Disorder (IPD): Analysis in Educational Guidance and Counseling - Kurnanto, Muhammad Edi; bin Kamaruddin, Mohd Shahrul; Yahya, Fatahya; Sabil, Surena (Al-Hayat: Journal of Islamic Education, 2023)
With rapid technological advances, users worldwide have access to various data and content on the internet, including pornographic content. The availability of pornographic videos on the internet harms the morale and image of adolescents and adults of both sexes. This study aims to determine the gender-specific relationship between pornography motivation, sexual arousal, and sexual satisfaction with Internet Pornography-Viewing-Disorder (IPD). This type of research is quantitative. Convenience sampling was used in conducting the approach, and 202 participants filled out the distributed Google forms. The respondents of this study were online pornography users from Malaysia and Indonesia. Data was collected using an online questionnaire through social networking sites such as Twitter, Instagram, Facebook and Whatsapp. Data were analyzed using quantitative descriptive data analysis. This involves processing and presenting data in descriptive statistics such as frequency, percentage, mean, and standard deviation. This study provides an essential understanding of the role of sexual arousal and the desire to experience pleasure in viewing online pornography. The research results show that these factors have a significant influence as a motivator for individuals who engage in these behaviours. More specifically, these findings suggest that men are more driven by sexual arousal and the desire to seek pleasure when accessing online pornography. The implications of this finding are very relevant in educational guidance and counselling. In seeking to help individuals who engage in online pornographic behaviour, counsellors and educators must understand that sexual arousal and the desire to experience pleasure can act as powerful motivators. In counselling, it is necessary to consider how these factors can influence individual behaviour and psychological health.